Penilaian Kerentanan Air Permukaan terhadap Pencemaran di Sub DAS Garang Hilir Berbasis Multi-Indeks - Hermin Poedjiastoeti; Sudarmadji Sudarmadji; Sunarto Sunarto; Slamet Suprayogi (Jurnal Wilayah dan Lingkungan, 2017)
Assessing the surface water vulnerability to pollution in the Garang Downstream Watershed Semarang requires a study concerned with some environmental components/indicators. Vulnerability measurement through surface water susceptibility index formulation on pollution is important considering the absence of surface water pollution effect indicators in an efficient assessment system. Therefore, a multi-indicator vulnerability assessment on surface water pollution is necessary. The Surface Water Vulnerability Index to Pollution (SWVIP) is composed of five components, namely water quality (WQ), rainfall (R), land use and vegetation cover (LVC), river hydrogeometric (RH) and population (P). Regarding index development, the subindex graphs and the weighting of each component are created. The application of composite index measurement yields an equation of SWVIP = 0.29.WQI + 0.23PI + 0.14RI + 0.20.LVCI + 0.14.RHI and an index value of 73.87 including the "rather high" category that represents the "vulnerable"condition in the Garang Downstream Watershed Semarang. This suggests that the five selected components used in the index creation can provide useful information to decision making in the surface water pollution control.